FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK DENGAN PEREDARAN BRUTO TERTENTU MELALUI PENDEKATAN PERILAKU - Yoda Mustikasasti, Elvanes; Usman, Fadlil (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
This research is a survey conducted on taxpayers with specific gross circulation in the area of KPP Pratama Pondok Aren. The title of this research is "Factors Affecting Taxpayer Compliance with Specific Gross Circulation Through Behavioral Approach (Case Study at KPP Pratama Pondok Aren)".This study aims to determine the factors that influence taxpayer compliance with specific gross circulation according to PP 46 Tahun 2013.Sampling using simple random sampling with the Slovin method. From the calculation results obtained the number of samples is 100 respondents. The analytical tool in this study is multiple regression analysis which is used to see the factors that influence taxpayer compliance with specific gross circulation according to PP 46 Tahun 2013.The results of this study indicate that there are two factors that influence taxpayer compliance with spesific gross circulation according to PP 46 of 2013, namely attitude and religiosity.